(untitled) (Práxis Educativa, 2022)
The role of children’s and young adult literature in the construction of black children’s identities and in the establishment of positive ethnic-racial relationships still needs discussion and recognition. Therefore, this article aimed to promote some considerations about black authorship and the characterization of black characters in literary works. As powerful narratives for the inclusion of diversity Zum Zum Zumbiiiiiiiii and Olelê: an ancient song from Africa stood out. The study was based on bibliographical research, educational norms, Afrocentricity (ASANTE, 2009) and Afro-Brazilian civilizing values ​​(TRINDADE, 2010). Given what was analyzed, we verified the relevance of children’s and young adult literature on black themes in order to expand children’s perception of the world, respecting differences, valuing the history of the black population and racial identification. Keywords: Racial identity. Black authorship. Black thematic.